Можливості хірургічного лікування цукрового діабету 2-го типу - Грубнік, В. В.; Голляк, В. П.; Кресюн, М. С.; Воротинцева, К. О. (Clinical Endocrinology and Endocrine Surgery, 2013)
Type 2 diabetes mellitus (T2DM) is a global problem of world healthcare. In 2000, the disease struck about 171 million people around the world, the growth rate of this disease is very high, and by 2030 the number of patients with this condition will reach 366 million people. This is a heterogeneous disorder caused by deficiency of both insulin secretion and resistance of insulin. It is believed that one of the risk factors for type 2 diabetes is obesity – in 80-90% of patients with type 2 diabetes obesity occurs. Initially bariatric surgery is considered an effective method of weight loss in individuals with a BMI>40 kg/m2. However, it appeared that when the bariatric operations remission diabetes is fast enough even with a significant reduction of body weight. At present there are different types of surgery in the treatment of obese patients with type 2 diabetes. These include the operation of the decline in the stomach, malabsortive operation under which the intestinal bypass, and mixed types of transactions in which restrictive and malabsortive technology are combined. Type 2 diabetes is considered to be a disease of the pancreas. Combined bariatric surgery can significantly improve the treatment of this disease by affecting the intestinal factor of this disease.